2020
DOI: 10.1016/j.dsr.2020.103369
|View full text |Cite
|
Sign up to set email alerts
|

Evidences of human impact on megabenthic assemblages of bathyal sediments in the Alboran Sea (western Mediterranean)

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 86 publications
1
10
0
Order By: Relevance
“…Bo et al 13 reported the presence of I. elongata with healthy, tall (up to 36 cm), highly branched colonies, and an average density of 0.5 ± 0.04 col. m −2 and maximum values of 2.7 col. m −2 . These density values are comparable to those found in this study and with those reported by Grinyó et al 42 for bathyal soft bottoms in the Alboran Sea, where I. elongata reached a maximum density of 7 col. m −2 . Other data from the Mediterranean Sea acquired by ROV-imaging showed that in the Balearic Sea, different values of density were reported when comparing untrawled and trawled bottom areas: 0.23–0.27 col. m −2 and 0.0053–0.0062 col. m −2 , respectively 21 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Bo et al 13 reported the presence of I. elongata with healthy, tall (up to 36 cm), highly branched colonies, and an average density of 0.5 ± 0.04 col. m −2 and maximum values of 2.7 col. m −2 . These density values are comparable to those found in this study and with those reported by Grinyó et al 42 for bathyal soft bottoms in the Alboran Sea, where I. elongata reached a maximum density of 7 col. m −2 . Other data from the Mediterranean Sea acquired by ROV-imaging showed that in the Balearic Sea, different values of density were reported when comparing untrawled and trawled bottom areas: 0.23–0.27 col. m −2 and 0.0053–0.0062 col. m −2 , respectively 21 .…”
Section: Discussionsupporting
confidence: 93%
“…According to Pérès and Picard 15 , I. elongata is associated with compact mud. Further studies are needed to clarify whether potential differences in the physical, geological, and geochemical characteristics of sediments (e.g., grain size, porosity, water content, composition, and organic content) can contribute to driving the distribution of Isidella facies 42 . www.nature.com/scientificreports/ and fly-tipping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have focused on assessing the actual environmental status of mesophotic ecosystems and, thus, on collecting the quantitative information needed to determine the baseline for developing appropriate conservation policies and future monitoring activities. The increase of human impacts, mainly due to fishing pressures and uncontrolled litter disposal, is leading to the severe degradation of these important mesophotic ecosystems [1,51,52], stressing the need to enforce control and surveillance measures to improve and preserve the "Good Environmental Status" of mesophotic coral forests under European marine legislations. While shallower ecosystems, such as coastal mangroves and seagrasses, as well as deeper, cold-water coral reef habitats, are currently under several monitoring and protection measures for the maintenance and restoration of these ecosystems [53,54], only a few conservation initiatives are explicitly aimed at the protection of deep circalittoral assemblages from destructive practices, such as fishing activities [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…However, this also results in high levels of bycatch that can account for up to 65% of total catch including the exploitation of juvenile and undersized individuals (Maynou et al, 2021; Tsagarakis et al, 2014). Indiscriminate trawling practices have also resulted in substantial alterations in benthic community composition in this region with many VME indicator species now largely absent from these areas (De la Torriente Diez et al, 2022; Grinyó et al, 2020; Pierdomenico et al, 2018). Seamounts in this region have also been shown to serve focal roles for a diverse range of threatened top predators that are vulnerable to capture in trawl nets, and so these features deserve increased attention in future marine spatial planning discussions (Bo et al, 2021; Vassallo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%